2003
DOI: 10.1016/s0378-1097(03)00430-0
|View full text |Cite
|
Sign up to set email alerts
|

F factor conjugation is a true type IV secretion system

Abstract: The F sex factor of Escherichia coli is a paradigm for bacterial conjugation and its transfer (tra) region represents a subset of the type IV secretion system (T4SS) family. The F tra region encodes eight of the 10 highly conserved (core) gene products of T4SS including TraAF (pilin), the TraBF, ‐KF (secretin‐like), ‐VF (lipoprotein) and TraCF (NTPase), ‐EF, ‐LF and TraGF (N‐terminal region) which correspond to TrbCP, ‐IP, ‐GP, ‐HP, ‐EP, ‐JP, DP and TrbLP, respectively, of the P‐type T4SS exemplified by the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
430
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(443 citation statements)
references
References 110 publications
8
430
0
3
Order By: Relevance
“…1 Over 75 VirB6-like proteins have been identified, all of which are known or postulated components of T4SS. 2,34 Despite overall low sequence similarities, VirB6-like proteins are highly hydrophobic with multiple predicted membrane-spanning segments. 2,34 Previous studies showed that several VirB proteins are rapidly degraded in virB6 null mutants, implicating VirB6 as important for assembly of a stable secretory apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Over 75 VirB6-like proteins have been identified, all of which are known or postulated components of T4SS. 2,34 Despite overall low sequence similarities, VirB6-like proteins are highly hydrophobic with multiple predicted membrane-spanning segments. 2,34 Previous studies showed that several VirB proteins are rapidly degraded in virB6 null mutants, implicating VirB6 as important for assembly of a stable secretory apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…2,34 Despite overall low sequence similarities, VirB6-like proteins are highly hydrophobic with multiple predicted membrane-spanning segments. 2,34 Previous studies showed that several VirB proteins are rapidly degraded in virB6 null mutants, implicating VirB6 as important for assembly of a stable secretory apparatus. 33,35,36 With the TrIP assay (this work), 16 we now have shown unequivocally that VirB6 participates directly in substrate trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest subfamily, the conjugation systems, are found in most species of Gram-negative and Grampositive bacteria. These systems mediate DNA transfer both within and between phylogenetically diverse species, and some systems even deliver DNA to fungi, plants and human cells 2,[9][10][11][12][13] . Conjugation is an important contributor to genome plasticity, and therefore bacterial fitness under changing environmental conditions, as encountered during infection of the human host.…”
Section: The T4s Familymentioning
confidence: 99%
“…The conjugative proficiency requires the expression of set of transmembrane proteins which are known collectively as type IV secretion systems (T4SS; Lawley, Klimke, Gubbins, & Frost, 2003). The presence of conjugative plasmids and the expression of conjugative machinery are detrimental for the host cell fitness (Rozkov et al., 2004), but there is no consensus on the valid ranges of metabolic costs imposed by the conjugative process.…”
Section: Example 3: T4ss Common Poolmentioning
confidence: 99%